The Prevalence of Carotid Artery Stenosis in Patients with Coronary Artery Disease - مدهن, طارق; باسم معروف (Latakia University Journal -Medical Sciences Series, 2024)
Background: Carotid Artery Stenosis is one of the main reasons for strokes. Patients with concomitant coronary and carotid artery disease are at risk of developing serious neurological events especially pre- and post coronary artery bypass graft operations. It's Important to recognize these patients in order to avoid these serious consequences The main aim of this study was to study the prevalence of carotid artery stenosis in patients with coronary artery disease, and to recognize the main risk factors that is associated with more advanced carotid artery disease. Methods: The study included 127 patients diagnosed with coronary artery disease by coronary artery angiogram (CAG) patients attending Tishreen University Hospital from November 2022 to November 2023. Results: carotid artery disease was found in 33% of patients with coronary artery disease, and 13% of patients appear to have significant carotid artery stenosis (>50%) The independent predictors of carotid artery stenosis was advanced age, hypertension, the severity and extent of coronary artery disease. Coronary artery scores derived from coronary artery angiogram ( SYNTAX, Gensini ) were highest in patients allocated to significant carotid stenosis. There was significant correlation between these scores and the severity of carotid artery stenosis. . Conclusion: Prevalence of carotid stenosis is high in patients with coronary artery disease. And screening of carotid artery stenosis is recommended especially in older patients with multivessel CAD. The Gensini score may be used to identify patients at high risk for significant carotid stenosis prior to CABG.